6ab + a(a – b – 6b) + 4a(2b +a) – ab , para a= -1 e b=2 ME AJUDEM! É URGENTE

Question

6ab + a(a – b – 6b) + 4a(2b +a) – ab , para a= -1 e b=2

ME AJUDEM! É URGENTE

in progress 0
Lệ Thu 6 months 2021-07-27T10:28:24+00:00 1 Answers 5 views 0

Answers ( )

    0
    2021-07-27T10:29:53+00:00

    Answer:

    -81

    Step-by-step explanation:

    replace the numbers you were given in a or b.

    so

    6(-12) -1(-1 – 2 – 6(2)) + 4(-1)(2(2) -1) -12

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )